Dímero D como factor pronóstico de gravedad en pacientes COVID-19 - Castillo-Huerta, Cristel; Castillo-Velásquez, Yiyo; Chávez-Cerna, Alicia; Cubas-Iparraguirre, Anibal; Vergara-de la Rosa, Esteban (Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo, 2021)
Carta al editor (sin resumen)